Penerapan Pembelajaran Tari Dengan Metode Demontrasi Menggunakan Media Aplikasi Whatsapp Di SMA Negeri 7 Padang - Maharani Antika Sari; Fuji Astuti (FBS Universitas Negeri Padang, 2021)
This research aims to explain and describe the use of demonstration method using WhatsApp application in class XI IPS 3 at SMA Negeri 7 Padang. This is a qualitative research. The evaluation of the students’ outcomes in this research consists of the evaluation of Knowledge (cognitive) and Dance Practice (psychomotor). The data used were primary and secondary data. The data were collected through literature, observation, and documentation/ shooting studies. The data was analyzed by using the percentage formula. The results of the study show that the implementation of demonstration method in Cultural Arts learning in class XI IPS 3 at SMA Negeri 7 was conducted in online learning. Both theory learning and dance practice could be carried out well. This is evidenced by the grades students got in the theory learning at the second meeting. The average score got is 78.7. Meanwhile, at the dance practice learning, students got 76.7 in the meeting 4. In addition, at the meeting 5, the score increases to 82.9. It can be concluded that the average psychomotor score of students at the end of the study is 79.8 and it is categorized good.